REALIZING ANTI-BULLIYING THROUGH HABITUATION ACTIVITIES “SAYBER PANCANGAN DOA” AS AN EFFORT TO IMPROVE CHARACTER EDUCATION - Edy Prayoga; Sri Harini; Suci Hidayati (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2023)
Post-pandemic online learning raises the problem of declining character values such as decreased self-confidence, concern for the environment, selfishness, and empathy for others. This makes educational institutions have the tough task to restore the identity of their students. One of the efforts made by the Head of SMKN 1 Turen Malang Regency to minimize the above problems is to carry out character education habituation activities called "Sayber Pancangan Doa". The number of respondents in this study was 1,988 students with 58 parallel classes who were observed 116 times within three months. The results showed that there was a change in anti-bullying behavior with a percentage of 6.53% to 100% and the formation of character values in students with good categories for each indicator of Sayang, Clean, Smart, Beautiful, Handsome, and Do'a. The conclusion is that the habituation activities of "Sayber Pancangan Doa" that have been implemented have a positive effect on changing students' behavior, anti-bullying, and increasing the value of their social and religious character. It is hoped that the habituation activity "Sayber Pancangan Doa" can realize anti-bullying behavior in all students so that the learning process at SMKN 1 Turen runs safely, comfortably, and protected from bullying practices.Post-pandemic online learning raises the problem of declining character values such as decreased self-confidence, concern for the environment, selfishness, and empathy for others. This makes educational institutions have the tough task to restore the identity of their students. One of the efforts made by the Head of SMKN 1 Turen Malang Regency to minimize the above problems is to carry out character education habituation activities called "Sayber Pancangan Do'a". The number of respondents in this study was 1,988 students with 58 parallel classes who were observed 116 times within three months. The results showed that there was a change in anti-bullying behavior with a percentage of 6.53% to 100% and the formation of character values in students with good categories for each indicator of Sayang, Clean, Smart, Beautiful, Handsome, and Do'a. The conclusion is that the habituation activities of "Sayber Pancangan Do'a" that have been implemented have a positive effect on changing students' behavior, anti-bullying, and increasing the value of their social and religious character. It is hoped that the habituation activity "Sayber Pancangan Do'a" can realize anti-bullying behavior in all students so that the learning process at SMKN 1 Turen runs safely, comfortably, and protected from bullying practices.